Complications in Posterior Cranial Vault Distraction. Issue 2 (February 2016) - Greives, Matthew R.; Ware, Benjamin W.; Tian, Ashley G.; Taylor, Jesse A.; Pollack, Ian F.; Losee, Joseph E.
Abstract : Background: The use of posterior cranial vault distraction for the treatment of elevated intracranial pressure is gaining popularity and is a standard for first-stage cranial expansion in syndromic craniosynostosis at many institutions. However, although the operation is faster and less complex than other cranial vault remodeling procedures, it is not without its own unique set of complications. Methods: We surveyed the published literature for case series and case control studies on posterior vault distraction. Complication rates and types for these series were tabulated and grouped by management. When outcomes were unclear, corresponding authors were contacted for clarification and treatment plans. Results: Eleven reports were found from a search of all the literature on posterior cranial vault distraction with a range of 1 to 22 included patients. The average age at surgery was 16.2 ± 11.8 months. Complication rates ranged from 12.5% to 100%, with the average of 30% of patients across all studies. The most common complications reported were cerebrospinal fluid leak or dural injury, followed by wound infections or device exposures, and device failure. There were no reported patient deaths or long-term morbidities. Conclusions: Posterior cranial vault distraction is a relatively safe and effective therapy for the treatment of elevated intracranial pressure in the setting of syndromic craniosynostosis. The majority of described complications center on the interaction of the device with the dura, device extrusion, and infection. Extreme care must be used with the placement of these distraction devices and with handling of the dura at the osteotomy sites to ensure successful outcomes and avoid complications. Levels of Evidence: III